2021
DOI: 10.3390/healthcare9060699
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nurse-Led Intervention Programs Based on Goal Attainment Theory: A Systematic Review and Meta-Analysis

Abstract: This study aimed to evaluate the effects of the goal attainment theory-based nurse-led intervention programs using a systematic review and meta-analysis. Randomized and non-randomized controlled trials, published from January 2001 to December 2020, were examined using four international databases and four domestic databases. The search, selection, and coding were performed independently by two researchers. R version 4.0.3 and Review Manager (version 5.3) were employed for meta-analysis and quality assessment, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Hence, it is essential to outline the implementation conditions and any adaptations that are made. In studies that analyse implementation conditions, the impact of a programme is often related to its intensity or duration (Arnason et al, 2020;Park, 2021). Thirdly, the "high systematization" programmes are characterized by a higher percentage of institutional support.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, it is essential to outline the implementation conditions and any adaptations that are made. In studies that analyse implementation conditions, the impact of a programme is often related to its intensity or duration (Arnason et al, 2020;Park, 2021). Thirdly, the "high systematization" programmes are characterized by a higher percentage of institutional support.…”
Section: Discussionmentioning
confidence: 99%
“…With the exception of the general characteristics of implementations, which are widely described in review studies (e.g., Gilligan et al, 2019;Li et al, 2021;Park, 2021), few results are reported on aspects relating to the institutional and external support that is required to boost the effectiveness of implementations. This leads to a current dilemma on the scientific dissemination of evidence-based programmes.…”
Section: Scaling Up In Communities and Services In Family Support Pro...mentioning
confidence: 99%
See 1 more Smart Citation
“…Umboh Morenita Jeanifer 1 , Ati Surya Mediawati 2 , Irman Somantri 3 -The Effect of the SDKI, SLKI ….. clinical practice(Park, 2021) Tanrewali et al (2023). said implementing 3S (SDKI, SLKI, SIKI) is based on evidence-based practice on the quality of nursing services before and after assistance.…”
mentioning
confidence: 99%